PILKADA SERENTAK DARI PERSPEKTIF KONFLIK - Fanila Kasmita Kusuma (Media Keadilan: Jurnal Ilmu Hukum, 2018)
This article discusses simultaneous local elections from a conflict perspective. The process of democracy (electoral), conflict is a necessity because every individual or social group has different interests, understandings, and values. Conflict is relatively easy to come from more complex social bases. Democracy is also believed to be a means of transforming conflict. The research method used is normative legal research, with a statute approach and conceptual approach. Analyzed descriptively qualitatively. As for the results of research, that democracy seeks to transform conflict in the form of violence toward the voting booths, from coercive to persuasive. However, democracy and conflict are actually two things that are not easily connected. From many experiences, it is not easy to prove that democracy can be a trigger for conflict, although it can be claimed that the escalation of conflict is caused by political liberalization at work in the democratic process. The existence of a natural conflict for a democratic process. It becomes dangerous if the conflict is repressive and takes the form of violence.Keywords: conflict; simultaneous local election.AbstrakArtikel ini membahas tentang pilkada serentak dari perspektif konflik. Proses demokrasi (elektoral), konflik merupakan sebuah keniscayaan karena setiap individu atau kelompok sosial memiliki kepentingan, pemahaman, dan nilai yang berbeda-beda. Konflik relatif mudah hadir dari basis sosial yang lebih kompleks. Demokrasi juga diyakini sebagai sarana untuk mentransformasikan konflik. Metode penelitian yang digunakan adalah penelitian hukum normatif, dengan statute approach dan conceptual approach. Dianalisis secara  deskriptif kualitatif. Adapun hasil penelitian, bahwa demokrasi berupaya mentransformasikan konflik yang berwujud kekerasan ke arah bilik suara, dari memaksa (coercive) ke persuasif. Meski demikian, demokrasi dan konflik sebenarnya juga merupakan dua hal yang tidak mudah dihubungkan. Dari banyak pengalaman yang ada, bukan hal yang mudah membuktikan bahwa demokrasi dapat menjadi pemicu konflik, walaupun dapat diklaim bahwa eskalasi konflik disebabkan oleh liberalisasi politik bekerja dalam proses demokrasi. Eksistensi konflik wajar bagi suatu proses demokrasi. Menjadi berbahaya jika konflik sudah represif dan berwujud kekerasan (violence).Kata kunci: konflik; pilkada serentak.